Editorial - Soares, Adriana Benevides; Tsallis, Alexandra Cleopatre; Mendes, Deise Maria Fernandes; Barros, Rita Maria Manso de (Estudos e Pesquisas em Psicologia, 2014)
Adriana Benevides Soares, Alexandra Cleopatre Tsallis, Deise Maria Fernandes Mendes, Rita Maria Manso de Barros